Temporal and spatial patterns of sediment deposition in the northern South China Sea over the last 50,000 years - Liu, Jianguo; Steinke, Stephan; Vogt, Christoph; Mohtadi, Mahyar; De Pol Holz, Ricardo Hernán; Hebbeln, Dierk (My University, 2017)
Sediment depositional patterns along the upper continental slope of the northern South China Sea (SCS) have been studied using two sediment cores (GeoB16601-6, 20 degrees 09.07'N, 116 degrees 14.38'E, 1012 m water depth and GeoB16602-4, 18 degrees 57.12'N, 113 degrees 42.64'E, 951 m water depth) recovered during RV SONNE Cruise SO-221 "INVERS". Sediment cores were analyzed for bulk sediment element composition by X-Ray Fluorescence (XRF) core scanning and clay mineral assemblage by X-Ray Diffraction (XRD). The bulk sediment element and the clay mineral compositions of the two cores suggest similar depositional patterns between 50 kyr BP and similar to 29 kyr BP, and similar to 14 kyr BP to present, but a clear difference in depositional patterns during the last glacial and deglacial (similar to 29-14 kyr BP) when sea level was below 90 m. Between similar to 29-14 kyr BP, a higher kaolinite percentage in core GeoB16602-4 in comparison to core GeoB16601-6 is interpreted to reflect a higher contribution of clay supplied by the Pearl River to core site GeoB16602-4. In contrast, core GeoB16601-6 received less Pearl River supplied clayey material during the same period. When the sea level was below 90 m during the last glacial lowstand, the detrital fine-grained materials supplied by the Pearl River were mostly transported by coastal currents to the southwest, resulting in a higher contribution of Pearl River discharged material at site GeoB16602-4 than at site GeoB16601-6. We suggest that sea-level induced modifications of the land-ocean distribution together with changes in the palaeo-physiographic conditions, such as the proximity of the palaeo-rivers to the individual core sites might be responsible for the different sediment depositional patterns in the study area. Thus, the overriding control of sea-level induced changes on the sediment depositional environment might mask climate-related changes in sediment depositional pattern in the northern SCS. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: south china sea; holocene; last glacial maximum; sea level; pearl river; clay minerals